Designing a polarization‐insensitive and ultra‐wideband transmissive polarization convertor using a tightly coupled dipole array. Issue 1 (19th October 2022) - Kim, Seongjung; Nam, Sangwook
Abstract: In this study, a polarization‐insensitive and ultra‐wideband transmissive polarization convertor (PC) is proposed. The proposed PC operates at 2.29–6.27 GHz (93.32%) for the same polarization reflection at ≤−10 dB, orthogonally rotated polarization transmission at ≥−1 dB, and a 0.22 λlow thickness at the lowest operating frequency. A dual‐polarized tightly coupled dipole array (TCDA) antenna is introduced for application in the wideband PC, where the operating bandwidth is related to the antenna bandwidth. Additionally, the polarization insensitivity is related to the feeding structure, which allows coupling of the receiving signal to the transmitting antenna. Furthermore, the operating principle is described in detail by showing the surface current on the TCDA and the feeding structure. Finally, unit cell simulations and measurements are presented to demonstrate the performance of the proposed PC.